2016
DOI: 10.3390/agronomy6010004
|View full text |Cite
|
Sign up to set email alerts
|

Novel QTL for Stripe Rust Resistance on Chromosomes 4A and 6B in Soft White Winter Wheat Cultivars

Abstract: Stripe rust (caused by Puccinia striiformis f. sp. tritici) of wheat (Triticum aestivum) is a devastating disease in temperate regions when susceptible varieties are grown and environmental conditions sustain high disease pressures. With frequent and severe outbreaks, disease resistance is a key tool for controlling stripe rust on wheat. The goal of this research was to identify quantitative trait loci (QTL) involved in stripe rust resistance from the important US Pacific Northwest soft white winter wheat vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 42 publications
4
17
0
Order By: Relevance
“…However, no available information about the reaction of these two genes against the Egyptian stripe rust race. In addition, many studies mapped novel QTLs controlling adult stage stripe rust resistance to this chromosome which con rming our ndings [45][46][47].…”
Section: Discussionsupporting
confidence: 85%
“…However, no available information about the reaction of these two genes against the Egyptian stripe rust race. In addition, many studies mapped novel QTLs controlling adult stage stripe rust resistance to this chromosome which con rming our ndings [45][46][47].…”
Section: Discussionsupporting
confidence: 85%
“…Yadav et al [19] used 210 F 2 and 150 BC 1 F 2 mapping population to map QTLs governing the sheath blight resistance in rice. Similarly, Klarquist et al [8] used 151 F 2:5 RIL populations to identify and map QTLs involved in stripe rust resistance in wheat. Moreover, Perchepied et al [20] mapped two new pear resistance loci using three F 1 segregating populations (182, 144 and 81).…”
Section: Genetic Mapping/linkage Mapping Of Genes/qtlsmentioning
confidence: 99%
“…Recently, molecular techniques like molecular markers and genetic engineering are widely used for rapid and efficient accumulation of novel resistant genes from various sources into a single background to produce broad spectrum/ durable resistance in crop plants [1,8,10].…”
Section: Pyramiding Of Genes /Qtls For Biotic Stress Resistancementioning
confidence: 99%
See 1 more Smart Citation
“…The results of the QTL analysis showed that QYrel.wak-4A and QYrfi.wak-6B reduced infection type and disease severity. Based upon both molecular and phenotypic differences, QYrel.wak-4A is a novel QTL for adult plant resistance (APR) to stripe rust (Klarquist et al, 2016).…”
Section: Genetic Mapping Of a Putative Thinopyrum Intermedium Derivedmentioning
confidence: 99%